Enhancing photocatalytic ability of titanium dioxide through incorporation of mil-53(FE) towards degradation of methyl orange and methylene blue - Nurul Wafa Othman (2017)
MIL-53(Fe) is an iron(III) carboxylate compound fall under the subclass of metalorganic frameworks (MOFs). This compound was incorporated to TiO2, a non-toxic and highly efficient semiconductor for photocatalysis application. MIL-53(Fe) was synthesized by reflux method for 3 hours. The obtained MIL-53(Fe) powder was dispersed in ethanol and water mixture, sonicated and injected with a titanium(IV) butoxide. The mixture was then further heated in Teflon-lined autoclave to produce MIL-53(Fe)/TiO2. To produce MIL-53(Fe) derived Fe2O3/TiO2 composite, the powder was calcined at 500 °C. XRD pattern confirmed the obtained powder corresponds to the MIL-53(Fe)/TiO2 with characteristic feature of an anatase and MIL-53(Fe), while the XRD pattern of the calcined MIL-53(Fe)/TiO2 powder suggested that the derived material were Fe2O3/TiO2 composite. EDX data proved that there was MIL-53(Fe) material incorporated to the TiO2. Scanning Electron Microscope (SEM) image of MIL- 53(Fe) showed a triangular prism-shaped with particle size in the range of 0.2 to 0.25 μm. A spherical morphology were observed on MIL-53(Fe)/TiO2 and MIL-53(Fe) derived Fe2O3/TiO2 composites with the particle size in the range of 0.73 to 0.94 μm and 0.61 to 0.81 μm respectively. The photocatalytic activity of photocatalyst MIL- 53(Fe)/TiO2, MIL-53(Fe) derived Fe2O3/TiO2 and a control sample of TiO2 nano powder were evaluated towards methyl orange (MO) and methylene blue (MB) dye in water under UV-vis light irradiation at different time interval for 6 hours time. The results revealed that both MIL-53(Fe)/TiO2 and MIL-53(Fe) derived Fe2O3/TiO2 materials exhibit better photocatalytic activity compared to the bare TiO2. MIL- 53(Fe)/TiO2 has slightly increased the photocatalytic performance of TiO2 for about 6% towards MO and 11% towards MB while MIL-53(Fe) derived Fe2O3/TiO2 has successfully increased the photocatalytic performance of bare TiO2 for about 75% in MO and 30% in MB dye. The results obtained show that, the MIL-53(Fe) derived Fe2O3/TiO2 has good photocatalytic degradation efficiency compared to MIL- 53(Fe)/TiO2. This implies that MIL-53(Fe) derived Fe2O3/TiO2 is a potential material for environmental remediation such as water purification and air purification.